Bad habits ; IVth degree burns ; Prison without bars [videorecording] - Lazaro, Cheche (Quezon City Probe Productions, 1994)
Documents the violence created by the Abu Sayaff group in Basilan; the U.P. College of Medicine graduating class with their "sunugan"; and the Iwahig Penal Colony in Palawan.
Bad habits (14 min) -- IVth degree burns (16 min.) -- Prison without bars (15 min).
VHS.
Reporter, Marga Ortegas.
Keywords: Iwahig Penal Colony (Palawan).; Violence -- Philippines -- Basilan; Interns (Medicine) -- Philippines -- Manila; Penal colonies -- Philippines -- Puerto Princesa (Palawan).